Photoluminescence studies of TM and RE doped oxides using diamond anvil cell - Kamińska, Agata (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
The present status of high-pressure research with the diamond anvil cell (DAC) is described, focusing mainly on use of this technique in optical spectroscopy. After a brief description of the history of the development of high-pressure measurements, the principles of DAC technique are described in more detail. Then different applications of this technique to high-pressure research are discussed, including optical spectroscopy, electrical measurements, X-ray diffractometry and other measurements. Results obtained for selected materials, with a view to illustrating the physics behind high-pressure phenomena, are presented and discussed. These include high-pressure luminescence studies of Cr3+ or Yb3+-doped lithium niobate crystal (LiNbO3) as well as Cr3+ and Nd3+-doped lanthanum lutetium gallium garnet crystal (La3Lu2Ga3O12). Finally, the boundary of high-pressure spectroscopy usefulness is shown. The example of such a case is the study of Cr3+-doped MgO-2.5Al2O3 non-stoichiometric green spinel.
Optica Applicata, Vol. 36, 2006, nr 2-3, s. 163-179
Keywords: optyka; diamond-anvil cells; high pressure; LiNbO3; Cr3+ dopant; luminescence; garnet crystals; ingomogenous broadening; Yb3+ ions; f-d transitions; spinel